Short-wavelength light induces broiler’s behavioral and physiological syndrome through a misaligned eating rhythm - Yang, Yefeng; Liu, Qiong; Wang, Shouyi; Zeng, Li; Pan, Chenghao; Jado, Ahmed; Elhadidi, Yasser; Liu, Kai; Pan, Jinming (International Journal of Agricultural and Biological Engineering, 2022)
Previous work shows that long-wavelength light has a robust circadian rhythmic pattern in the expression of clock genes of chickens, whereas short-wavelength light leads to an arrhythmic oscillation of some clock genes (e.g., cClock, cCry1, cCry2, cPer2, and cPer3). However, knowledge about the consequences of LED lights on the physiological and behavioral phenotype was still not clear. This experiment hypothesizes that short-wavelength light disturbs chickens’ eating rhythm and leads to the wrong time to eat, resulting in metabolic syndrome. “Meihuang” broilers were housed in monochromatic LED blue light, green light, yellow light, red light, or white light with a very low dose (15 lx). Multiply physiological parameters were measured and the 24-h eating behavior was determined. The effects of LED light on physiological status and behavioral phenotype showed a wavelength-dependent manner. Short-wavelength light significantly decreased the level of total triglycerides and total cholesterol but increased triiodothyronine concentration. Inversely, long-wavelength light increased the triglycerides and total cholesterol and reduced the level of triiodothyronine. Further, it was found that short-wavelength light significantly boosted body weight compared with long-wavelength light, despite equivalent levels of food intake. Short-wavelength light-induced 23.4% and 14.1% of food consumption during subjective nights, but long-wavelength light did not. These results imply that when chickens eat matters, not just what they eat. Thus, low as 15 lx of blue light exposure during the typical dark period is sufficient to lead an individual to eat at the “wrong” time, causing metabolic dysfunction. Blue light should be cautiously considered to be used in the poultry breeding process.Keywords: short-wavelength light, broiler, behavior, physiology, environmental control, circadian rhythm, intermittent eatingDOI: 10.25165/j.ijabe.20221503.6456Citation: Yang Y F, Liu Q, Wang S Y, Zeng L, Pan C H, Jado A, et al. Short-wavelength light induces broiler’s behavioral and physiological syndrome through a misaligned eating rhythm. Int J Agric & Biol Eng, 2022; 15(3): 47–54.